Sintesis Biosorben dari Cangkang Kelapa Sawit Melalui Modifikasi Permukaan Kimia dengan Naoh untuk Adsorpsi Air Water Treatment Plant Unit Sand Filter - Fithry, Dwi Annisa; Sitorus, Oby Vijay; Asri, Muhammad Alif (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Indonesia, as the world's largest palm oil producer, generates approximately 26 million tons of palm shell waste annually. This study aimed to evaluate the effect of contact time of NaOH-activated palm shell biosorbent on reducing water quality parameters in the WTP (Water Treatment Plant) sand filter unit at PKS PTPN IV Regional 3. Palm shells were prepared through washing, drying at 105°C, grinding, and sieving at 100 mesh. Chemical activation using 1 M NaOH for 2 hours without carbonization process resulted in increased material porosity. Adsorption testing was conducted at contact times of 30, 60, 90, and 120 minutes with adsorbent dosage of 10 grams per 100 mL water sample. Results showed that adsorption efficiency for Fe parameter reached 88-95% at 90 minutes contact time, turbidity reached 85-93% at 60 minutes, pH increased from 5.5 to 6.5-7.0, and TDS decreased from 27 to 25 mg/L. Kinetic analysis indicated that adsorption followed the pseudo-second-order model with determination coefficient R² = 0.998 for Fe and R² = 0.999 for turbidity, indicating chemisorption mechanism. Palm shell biosorbent without carbonization proved effective as an environmentally friendly alternative for water purification in palm oil industry WTP systems.